The predictive power of risk elicitation tasks - Michele Garagnani (University of Zurich, Department of Economics, 2020)
This work reports an online experiment with a general-population sample examining the performance of budget-choice tasks for elicitation of risk attitudes. First, I compare the investment task of Gneezy and Potters (1997) with the standard choice- list method of Holt and Laury (2002), and evaluate their performance in terms of the number of correctly-predicted binary decisions in a set of out-of-sample lottery choices. There are no significant differences between the tasks in this sense, and performance is modest. Second, I included three additional budget-choice tasks (selection of a lottery from a linear budget set) where optimal decisions should have been corner solutions, and find that a large majority of participants provided interior solutions instead, casting doubts on subjects' understanding of tasks of this type.
Keywords: C91; D81; C83; 330; risk preferences; elicitation methods; budget sets; portfolio choices